Photochemical growth of silver nanoparticles on c- and c+ domains on PZT thin films - Dunn, Steve; Jones, Paul M.; Gallardo, Diego E. (American Chemical Society, 2007)
The photochemical growth of silver nanoparticles on the negative domains of lead zirconate titanate thin films is reported. A sample of highly [100] orientated lead zirconate titanate, with a ratio of 30:70, that was 65−70 nm thick grown on Pt-coated MgO was poled by use of piezoresponse force microscopy to produce defined regions of surface positive and negative polarization. A comparison between the growth of silver nanoparticles on the surface of the lead zirconate titanate when illuminated with two sources of super band gap UV is given. In both cases the wavelength of illumination leads to growth on the positive domains but only illumination with a Honle H lamp, with a high photon output over 250−200 nm, caused significant growth of silver nanoparticles on the negative domain. The deposition on the negative domain is explained in terms of changed band bending due to the excitation of electrons into the conduction band, the rate of decay to the ground state, and dimensions of the ferroelectric film. The rate of deposition of silver nanoparticles on the negative domains is approximately half that on the positive domains.